EMMER WHEAT IS A PROMISING GRAIN CROP FOR ORGANIC AGRICULTURE - S. D. Gilev; I. N. Tsymbalenko; A. N. Kopylov; E. A. Filippova; T. A. Kozlova (Зерновое хозяйство России, 2018)
The article presents a short review of emmer wheat distribution throughout the whole world and the regions of Russia. The grain of emmer wheat is found rich in microelements, vitamins, nondispensible amino-acids and other useful substances. The article considers the two-year study results (2016, 2017) of the trials with emmer wheat on the central experimental plot of the Kurgansk RIA. Some separate elements of cultivation technologies of the emmer wheat variety ‘Gremme’ and the spring wheat variety ‘Zauralochka’ have been developed in three-year crop and fallow rotation on the extensive and intensive backgrounds. The variety ‘Gremme’ produced 3.4 t/ha being the largest yield during the trials, the spring wheat variety ‘Zauralochka’ gave only 2.98 t/ha. In the competitive variety-testing we studied comparative productivity of emmer wheat varieties ‘Gremme’ and ‘Runo’ with the spring wheat varieties ‘Tertsiya’ and ‘Iren’. The variety ‘Runo’ was found highly tolerant to powdery mildew, brown and stem rust, and grown without fertilizers and fungicides it was the most productive variety with 2.87 t/ha compared with the varieties ‘Tertsiya’, ‘Iren’ and ‘Gremme’ with 1.17, 1.26 and 1.72 t/ha respectively. According to the baking qualities, emmer wheat yielded to the spring wheat varieties. At the same time there is high protein content (17.5%) in the variety ‘Runo’. The preliminary results of the study show that the unhulled variety ‘Runo’ in the organic farming system claims to play a leading role in obtaining an environmentally clean grain rich in the necessary elements of nutrition.